Effectiveness of two systems for the spraying of pesticides in citrus trees - VELIZ, RUBÉN C.; GADANHA-JR., CASIMIRO D.; VÁSQUEZ-CASTRO, JAVIER A. (Revista Colombiana de Entomología, 2010)
Citriculture normally uses high application volumes in pesticide solutions (of 2.000 to 5.000 L ha-1) to control pests and diseases that affect the crop, which generates an increase in operational costs. For this reason, diverse systems of application are being developed to reduce application volumes and improve the uniformity of pesticide deposition. The goal of this work was to evaluate the efficiency of two application systems of pesticides in citrus trees. One system used a prototype for terrestrial application with rotary disc atomizers that are widely used in agricultural aviation, and the other system used hollow cone tip hydraulics. For the treatment of the trees the insecticide metidation was used at the dose of 180 gr per hectare. To study the droplet spectrum, water-sensitive papers were installed at different positions in the trees canopy, and for the study of insecticide deposition leaves of the treated plants were collected. The water- sensitive papers were collected and analyzed using a computerized image analysis system (e-sprinkle, EMBRAPA, sao Paulo, brazil), and the leaves analyzed by the technique of gas chromatography. Pesticide deposition was similar in both application system, although the solution volume used by the application system equipped with rotary disc atomizers was one quarter of the volume used by the application system equipped with hydraulic tips, reducing considerably the cost of the phytosanitary treatments.